2000
DOI: 10.1128/aem.66.7.2951-2958.2000
|View full text |Cite
|
Sign up to set email alerts
|

Gene Cloning and Expression and Secretion of Listeria monocytogenes Bacteriophage-Lytic Enzymes in Lactococcus lactis

Abstract: Bacteriophage lysins (Ply), or endolysins, are phage-encoded cell wall lytic enzymes which are synthesized late during virus multiplication and mediate the release of progeny virions. Bacteriophages of the pathogen Listeria monocytogenes encode endolysin enzymes which specifically hydrolyze the cross-linking peptide bridges in Listeria peptidoglycan. Ply118 is a 30.8-kDa L-alanoyl-D-glutamate peptidase and Ply511 (36.5 kDa) acts as N-acetylmuramoyl-L-alanine amidase. In order to establish dairy starter culture… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

7
78
0
2

Year Published

2006
2006
2018
2018

Publication Types

Select...
7
3

Relationship

0
10

Authors

Journals

citations
Cited by 129 publications
(89 citation statements)
references
References 48 publications
7
78
0
2
Order By: Relevance
“…lactis bacteriophage LL-H endolysin can be removed without destroying the lytic activity (85). C-terminal deletions of the Staphylococcus aureus bacteriophage endolysins PlyTW and Ply187, L. monocytogenes bacteriophage endolysin Ply511, Bacillus amyloliquefaciens phage endolysin Morita2001, Bacillus anthracis prophage endolysin PlyL, and Bacillus cereus phage endolysin Ply21 even increase the muralytic activity (50,83,(86)(87)(88). This pattern is also present in endolysins with dual lytic domains, for which, in theory, both should be equally active.…”
Section: Resultsmentioning
confidence: 83%
“…lactis bacteriophage LL-H endolysin can be removed without destroying the lytic activity (85). C-terminal deletions of the Staphylococcus aureus bacteriophage endolysins PlyTW and Ply187, L. monocytogenes bacteriophage endolysin Ply511, Bacillus amyloliquefaciens phage endolysin Morita2001, Bacillus anthracis prophage endolysin PlyL, and Bacillus cereus phage endolysin Ply21 even increase the muralytic activity (50,83,(86)(87)(88). This pattern is also present in endolysins with dual lytic domains, for which, in theory, both should be equally active.…”
Section: Resultsmentioning
confidence: 83%
“…Truncation of the endolysin to just the proposed catalytic domain produced an active lysin but did not affect the specificity. Other studies reported the maintenance of endolysin activity upon removal of C-terminal domains; in many cases, this truncation led to a notable increase in activity (9,14,28,32), while in others, activity remained similar to or was lower than that of the full-length endolysin (10,21). In several cases, endolysin catalytic domains retained the same or a similar host range upon removal of the C-terminal domain (9,18,28,32), despite the fact that their peptidoglycan target is usually shared with a number of other species.…”
Section: Discussionmentioning
confidence: 99%
“…Another technique of using lyisn is via lysin-secreting recombinant bacteria (Borysowski et al 2006). This was demonstrated in the case of recombinant Lactococcus lactis cells containing listerial lysin encoding genes to lyse L. monocytogenes in the surrounding medium (Gaeng et al 2000). This study also showed that the expression of functional lysin by L. lactis was detected in the presence of lactose that is used in milk fermentation.…”
Section: Application Of Phage Lysin In Foodmentioning
confidence: 57%